Vodou in Haitian Life and Culture
XIV, 242 p.
Keywords: This collection introduces readers to the history and practice of the Vodou religion, and corrects many misconceptions. The book focuses specifically on the role Vodou plays in Haiti, where it has its strongest following, examining its influence on spiritual beliefs, cultural practices, national identity, popular culture, writing and art.